Unraveling a Diagnostic Dilemma: Coexisting Metastatic and Tuberculous Cervical Lymph Nodes in a Post-Ablative Thyroid Carcinoma Patient – A Case Report on Uncommon Dual Pathology (Bangladesh Journal of Nuclear Medicine, 2025)
Tubercular lymphadenitis can mimic cervical lymph node metastasis from papillary thyroid carcinoma (PTC) due to similarities in the distribution and imaging characteristics of the affected lymph nodes. Here we report a rare case of simultaneous metastatic deposits and tuberculosis (TB) within the cervical lymph nodes of a patient with thyroid carcinoma after 5 years of radioiodine ablation.Bangladesh J. Nuclear Med. 27(2): 313-316, 2024